World economic and social survey - United Nations; United Nations (New York : United Nations, 1994)
Examining the current world-wide economic slump, this report assesses the state of the world economy and the role of public-private interaction in addressing the challenges of globalization. The book provides both global and regional perspectives on the economy, emphasizing the role of international trade and finance. It then discusses the changing role of the state, focusing on privatization, subsidized agricultural research, and state regulation of privately operated electrical utilities.
Latest issue consulted: 2004.
2003 - Trends and policies in the World economy.
oif 15/09/15
Ref.
Keywords: Economic history; Economic geography; Economic surveys; Economic development